Assessment of Genetic Diversity in Robusta Coffee Using Morphological Characters. Issue 3 (3rd July 2019) - Akpertey, Abraham; Anim-Kwapong, Esther; Ofori, Atta
ABSTRACT: Assessing the level of genetic variation that exist in any breeding population is important as this has significant implications for selection and variety development. The objectives of the present study were to determine the variation among 71 Robusta coffee genotypes based on 21 traits and to determine the genetic relationships between the genotypes. The 71 genotypes were established in 2013 as clones raised from single node cuttings and planted in a randomized complete block design with four blocks, with five plants per genotype per block. There was variation in all the traits assessed for the different Robusta coffee genotypes as evidenced by the coefficient of variation and frequencies of the quantitative and qualitative traits, respectively. Principal Component Analysis (PCA) was performed to obtain information on the relative importance of the morphological characters assessed, and cluster analysis was used to determine relationships among the genotypes evaluated. The first and second principal components accounted for 39.2% and 18.9% of the total variability, respectively. PCA revealed that height, stem diameter, span, number of laterals per tree, diameter of laterals, and number of nodes per lateral were the principal characters to discriminate the Robusta coffee genotypes examined. Cluster analysis grouped the Robusta coffee genotypes into five clusters as revealed by the dendrogram. The diversity among the Robusta coffee genotypes in both quantitative and qualitative traits revealed by this study can be used for trait improvement through selection and hybridization.